JASMINE’S FAIL ATTEMPT TO ACHIEVE ‘TRANSCENDENCE’ AS A FORM OF HER INTERNALIZATION AS ‘THE OTHER’ IN BLUE JASMINE (2013) - Veneralda, Livina; Mintarsih, Adriana Rahajeng (International Review of Humanities Studies, 2019)
Although there have been more Hollywood movies having their stories centered on female characters, their representation in Hollywood cinema is still problematic as most of these female characters do not become subjects in their own stories. They often internalize the notion of women as the Other. According to Beauvoir (2010), since women are deemed to be the Other, they become inessential part of the society. In the movie Blue Jasmine (2013), Jasmine has no power to design and lead her future as she subjugates herself to men. Then when she tries to free herself from this situation, she experiences oppression that comes from a male higher-up. Using textual analysis to analyze this character, this paper found that what she experiences represents women‟s everyday struggles in the society which resembles Beauvoir‟s concept of immanence and transcendence. Jasmine initially is stuck in immanence, when she depends on men, letting them have power over her. When she wants to take control over her own life, getting her independence, through education, she can achieve transcendence. However, this does not happen, and she falls back into the immanence instead because her environment makes it impossible for a woman to transcend. Moreover, this failure leads to her tragic ending which conveys a message that in the society women are bound to immanence.